Refined Guidelines for Selecting Hilal Observation Points in Tropical Regions: Insights from Bengkulu City - Taman, Badrun (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
This research evaluates the Bengkulu Provincial Government Mess as a potential site for rukyatulhilal, given that its selection has lacked a systematic, scientific foundation. The study focuses on three main aspects: first, the region’s geographical and astronomical characteristics; second, how well the chosen location aligns with established ideal parameters for crescent observation; and third, how site determination can be adapted to local conditions based on empirical findings. A qualitative approach grounded in geographical-astronomical analysis was employed. The results reveal that factors linked to the western horizon—specifically its alignment with the Indian Ocean at sea level—introduce notable meteorological disturbances, including high wave activity, strong sea breezes, and elevated water vapor content, all of which can impede visual detection of the hilal. Based on these insights, the study proposes updated criteria for selecting observation sites, recommending that optimal locations avoid a western horizon directly at sea level, particularly along the Indian Ocean frontage.